Trast indicators and the effect of reciprpcity in Internet auctions. Quantitative comparisons of behavior of buyers and sellers - Kozikowska Paulina (My University, 2007)
The Internet allows people to share freely their opinions in a community which build trust and reputation but also can be subjected to negative factors such as revenge and dishonesty. The Internet community which is analyzed in this thesis is the auction portal eBay. In this type of community feedback comments are a way of communicating and sharing opinions. The main focus of my analysis was to find out whether these comments have an impact on the participation of buyers and sellers in auctions and if they engage in reciprocal action. I prepared a survey for randomly picked buyers and sellers. The survey asked each group seven questions and was answered by 30 buyers and sellers, these answers were the basis for my empirical analysis. My analysis helped provide information about the importance of trust and reputation in this type of community.
Wskaźniki zaufania i efekt wzajemności w aukcjach internetowych. Porównania ilościowe zachowań osób kupujących i sprzedających
Keywords: internet auctions; eBay; Allegro; trust indicators; effect of reciprocity; buyers; sellers